Incidence, management and outcomes of prolonged second stage of labour in a rural setting in Malawi: a retrospective cohort study - Wouter Bakker; Elisabeth van Dorp; Timothy Phiri; Misheck Kazembe; Alfred Nkotola; Jos van Roosmalen; Thomas van den Akker (BMC Pregnancy and Childbirth)
Abstract Background Prolonged second stage of labour may lead to maternal and perinatal complications. Options for clinical management are augmentation with oxytocin, instrumental vaginal birth or second-stage caesarean section. We aimed to describe incidence, management and outcome of prolonged second stage of labour in a rural hospital in Malawi. Methods Retrospective analysis of medical records and partographs of all women who gave birth in 2015–2016 in a rural mission hospital in Malawi, comparing labour tracings with management protocols. Primary outcomes were incidence of prolonged second stage, instrumental vaginal birth and caesarean section. Furthermore, management and outcomes were assessed. Women arriving in hospital in the second stage of labour were compared to women arriving in an earlier stage of labour. Results Of all 3,426 women giving birth in the study period, 566 (16.5%) presented while already in the second stage. Based on their partographs, 307 (9.0% of 3426) were diagnosed with prolonged second stage. Of these women, 22 (7.2%) had labour augmented with oxytocin, 31 (10.1%) gave birth by vacuum extraction and 64 (20.9%) by caesarean section. Spontaneous vaginal birth occurred in 212 (69.0%). Women with prolonged second stage had an increased risk of having any complication, postpartum haemorrhage being the commonest. There was no difference in neonatal outcomes between women with or without a documented prolonged second stage. Of the 566 women presenting in the second stage, 538 (95.1%) had spontaneous vaginal births and 38 (6.7%) ended up having prolonged second stage registered in their partographs. Conclusion Prolonged second stage of labour was relatively common, and perhaps under-diagnosed due to a very sizeable proportion of women arriving whilst already in the second stage, of whom most gave birth spontaneously. Caesarean section occurred twice as often as vacuum extraction, suggesting a role for additional training and decision-making during childbirth to support the use of vacuum extraction.